Pre·Election coverage by SABC·TV of the 1989 General Election - John van Zyl (Communicare)
This article is based on the findings of a group of eleven specialists (WITS) who were commissioned by IDASA to monitor SABC-TV news coverage of the run-up to the 1989 general election. The report attempts to be a "case-study" In the construction of television news, employing discourse theory and the semiotics of film and communication In preference to the traditional quantitative approach. The encoding procedures of TV news were the main focus of the analysis which sought to demonstrate above all the shifting perspective within which news is constructed and how the signs and codes of news are closely related to those of fiction. It is freely acknowledged that the monitoring group occupied a position critical of the State and espoused a non-racist, non sexist, unitary political dispensation for South Africa, along the lines of the Freedom Charter.